The Way Forward in Sustainable Construction: Issues and Challenges - Jamilus Md Hussin; Ismail Abdul Rahman; Aftab Hameed Memon (International Journal of Advances in Applied Sciences, 2013)
Construction industry is one of the most significant industries that contribute toward socio-economic growth especially to developing countries. The nature of the industry are fragmented, unique and complex which always face chronic problems like time overrun (70% of projects), cost overrun (average 14% of contract cost), and waste generation (approximately 10% of material cost). It is also regarded as one of the largest polluters to our environment. Traditional practices of construction process and management are found unable to control unprecedented challenges including the carbon emission issue. These challenges accent the need for practitioners to rethink and improve the construction process and technology. This shows that the construction industry has a major potential in the advancement of sustainable development by addressing issues related to the economic, social, and environment. By adopting sustainable construction, it can reduce the overall energy use and maximize potential for renewable energy supply, minimize waste, conserve water resources, enhance water quality, incorporate water sensitive design and minimize vulnerability to flooding, minimize polluting emissions to water, air and soil and minimize noise and light pollution.